KKN Promotes a Clean Environment: Sorting, Composting, and Waste Facilities in RT.01, RW.01 Pematang Gubernur - Likasma, Fingkin; Sepliana, Rike; Riri, Alita; Juniar, Intan; Ramahdani, Dita; Wijaya, Ermy; Irwanto, Tito; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2025)
Due to population growth and wasteful consumption patterns that exceed management capabilities, waste has become a major problem in various communities, including in Indonesia. The accumulation of waste causes methane gas emissions, environmental pollution, and aesthetic and public health problems. The situation is exacerbated by the lack of facilities, integrated systems, and public awareness. Real Work Lecture (KKN) offers practical solutions and encourages strategic behavioral change. The purpose of this study was to determine how KKN impacts waste management in RT.01, RW.01 Pematang Gubernur, including sorting, composting, and utilization of waste facilities; in addition, to find factors that influence the success of the program. Planning, action, observation, and reflection are components of the participatory action research approach. The study will be conducted from June 11 to July 4, 2025 in RT.01, RW.01 Pematang Gubernur Village, Muara Bangkahulu District, Bengkulu City. Data were collected through documentation and in-depth interviews with community leaders and community representatives. Data analysis is a qualitative description technique in which data is reduced, presented in the form of narratives, descriptions, tables, or images, and then conclusions are drawn to ensure the sustainability of the program. The waste sorting program does many things, such as sorting organic and inorganic waste, making compost, and making trash bins. The purpose of this program is to increase public awareness, reduce the amount of waste disposed of at the landfill, and make the environment cleaner. The creation of organic and inorganic trash bins aims to facilitate waste sorting from the source and increase public awareness of responsible waste management. The KKN team also educates and facilitates household waste sorting. Compost is made with ash produced from burning organic waste to increase soil fertility and manage waste independently. As a result, this KKN program focuses on increasing public awareness and environmental cleanliness practices through household waste sorting, composting, and providing waste management facilities. It is hoped that this will result in a cleaner, healthier, and more sustainable environment in the community.